Perancangan dan Pengembangan Video Reportase Akreditasi Perguruan Tinggi Universitas Internasional Batam - Deli Deli; Eko Prastius (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
In Indonesia, accreditation is a one way to determine the quality standard of an educational institution, including universities. People often evaluate the quality of educational institutions based on the accreditation value. So in this study it can be shown that the value of accreditation is directly proportional to the quality of educational institutions. The accreditation process usually carried out within a period of 5 years and must be renewed at least 6 month before the expiration date. In this research, the author used qualitative methods to collect data on accreditation. The collected data from observation and documentation will be used to make a reportage video of the accreditation which will take place at Universitas Internasional Batam. The result of reportage video is available in two languages, English and Indonesian. The reportage video has an elements that are usually found in news videos, such as lower thirds, logos, and others. The reportage video in English has a duration of about 6 minutes 1 second and the reportage video in Indonesian has a duration of about 7 minutes 27 seconds. The reportage video is expected to help the development of universities and provide a legit information to wider community